Complete right bundle-branch block: echophonocardiographic study of first heart sound and right ventricular contraction times. Issue 6 (June 1979) - Brooks, N; Leech, G; Leatham, A
Abstract : High speed enchocardiograms of the mitral, tricuspid, and pulmonary valves were recorded with a simultaneous electrocardiogram and phonocardiogram in 20 patients with complete right bundle-branch block and in 67 normal subjects. Late opening of the pulmonary valve indicating late right ventricular ejection was found in all patients. In 8 patients with wide splitting of the first heart sound the late ejection was related mainly to delay in tricuspid valve closure, suggesting a late onset of the right ventricular pressure pulse. In 10 patients with a single first heart sound the delayed ejection was associated with a long interval between tricuspid valve closure and pulmonary valve opening, suggesting a slow rising right ventricular pressure pulse; 3 of these patients also had late tricuspid valve closure but the tricuspid component of the first sound was absent. Late onset of pressure rise is thought to result from block in the main right bundle-branch, and a slow rising pulse from block in the distal Purkinje network. These findings explain the conflicting results in previous studies of the first heart sound and right ventricular pressure pulse in patients with right bundle-branch block, and may have prognostic significance.